1983
DOI: 10.1111/1523-1747.ep12519287
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Arachidonic Acid Metabolism in UV-Irradiated Hairless Mouse Skin

Abstract: This study was conducted to investigate the metabolism of arachidonic acid in the skin of hairless mice exposed to UVA, PUVA, UVB, and UVC irradiation. The main products of arachidonic acid in the epidermis were hydroxyeicosatetraenoic acid (HETE), PGE2, and PGD2. Dermis displayed a lower lipoxygenase activity (expressed as HETE production) than the epidermis and showed no detectable cyclooxygenase activity, i.e., no prostaglandin production. The main changes observed in UV-induced inflammatory reactions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…UVB was also found to cause marked increases in PGJ 2 in keratinocytes, but to reduce PGD 2 production. Decreased production of PGD 2 is consistent with an earlier report demonstrating that UVB suppressed production of this arachidonic acid metabolite in hairless mouse skin (Ruzicka et al, 1983). PGD 2 is relatively unstable and degrades by spontaneous dehydration and isomerization reactions to PGJ 2 which is metabolized to a variety of biological active metabolites (Kikawa et al, 1984).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…UVB was also found to cause marked increases in PGJ 2 in keratinocytes, but to reduce PGD 2 production. Decreased production of PGD 2 is consistent with an earlier report demonstrating that UVB suppressed production of this arachidonic acid metabolite in hairless mouse skin (Ruzicka et al, 1983). PGD 2 is relatively unstable and degrades by spontaneous dehydration and isomerization reactions to PGJ 2 which is metabolized to a variety of biological active metabolites (Kikawa et al, 1984).…”
Section: Discussionsupporting
confidence: 91%
“…Each of these prostaglandins or their metabolites is known to be important in regulating cell growth, and their constitutive production in keratinocytes is presumably important in skin homeostasis (Fogh and Kragballe, 2000). As previously observed in mouse and human skin (Black et al, 1980b;Ruzicka et al, 1983), UVB stimulated production of PGE 2 in undifferentiated and differentiated cultures of primary mouse keratinocytes. PGE 2 is a potent proinflammatory mediator and it has been shown to play a key role in the development of UVB-induced skin cancer (Furstenberger et al, 1989).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, several studies showed that PGE 2 production is induced by numerous stimuli, including known skin tumor promoters such as UV irradiation (10,11) and 12-O-tetradecanoylphorbol-13-acetate (TPA; refs. 12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…As blocking of prostanoid production by treatment with nonsteroidal anti-inflammatory drugs (NSAIDs) treatment can abolish the immunosuppressive effect through UV (Chung et al, 1986;Hart et al, 2002;Walterscheid et al, 2002), it has been suspected that prostanoids play important roles in the UV-induced immunosuppression, especially in Treg induction. By UV radiation, various prostanoids are produced in the skin, with PGE 2 being the most abundant prostanoids (Kuwamoto et al, 2000;Ruzicka et al, 1983;Soontrapa et al, 2011). Recently, it has been revealed that PGE 2 -EP4 signaling mediates the induction of Treg by UV irradiation, and regulates UV-induced immunosuppression (Soontrapa et al).…”
Section: Prostanoids and Treg Inductionmentioning
confidence: 99%